(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Community service program to public This aim For increase capacity Mother House ladder in development and marketing product processed bamboo shoots based potential local in Bokak Village Sebumbun, District Sekadau Hilir, Regency Sekadau, West Kalimantan. Problems main issues faced public is low utilization bamboo shoots as product worth plus as well as limitations knowledge public regarding marketing strategies, in particular in aspect packaging, branding, and digital marketing. Activities implemented use approach participatory based community through stages counseling, training, mentoring, practice direct, as well as monitoring and evaluation. The program involves 20 housewives stairs that have interest in processing product local. Results of activities show existence improvement knowledge and skills participant in make packaging more products attractive and hygienic, arrange identity brand products, as well as utilize digital media such as WhatsApp Business, Instagram, and Facebook as means promotion. As many as 80% of participants capable make design packaging simple and operate social media For promotion product in a way independent. In addition, it is formed group business small based supportive community sustainability production and marketing product processed bamboo shoots. This program give impact positive to improvement quality product, expansion market access, as well as potential improvement income society. With thus, marketing strategy training based potential local can be one of approach effective in support empowerment economy public village.